Dynamic Analysis and Prediction of Food Nitrogen Footprint of Urban and Rural Residents in Shanghai - Xia, Yuling (Int J Environ Res Public Health, 2020)
The food nitrogen (N) footprint reflects the amount of reactive N emission and its impact on the environment as a result of food production and consumption to satisfy the basic food demands of an urban population. The N-Calculator model was used to estimate the food N footprint and its dynamic changes in Shanghai from 2000 to 2017, and the auto regressive integrated moving average (ARIMA) time series model was used to predict the food N footprint in Shanghai from 2018 to 2027. The results show that the food N footprint was higher in urban areas (15.3–18.8 kg N/capita/yr) than rural areas (12.6–17.4 kg N/capita/yr) of Shanghai from 2000 to 2017. The change in the food N footprint was consistent with changes in food consumption in urban and rural areas, and the total food N footprint of urban and rural residents was positively correlated with the per capita disposable income and population whereas it was negatively correlated with the Engel’s Coefficient and price index. It was predicted that the per capita food N footprint will gradually decrease in 2018–2027 in urban areas of Shanghai, but it will generally increase in the rural areas. This study will help to initiate policy interventions for sustainable N management and contribute to the achievement of key sustainable development goals (SDGs).